The utility of Fine Needle Aspiration Cytology in the Diagnosis of Lymphadenopathy - Dr. Annu Elizabeth Prakash; Dr. Navya Narayanano; Dr. Siyad Pokkakillath Mohamed; Dr. Rasmi Unnikrishnan (Tropical Journal of Pathology and Microbiology, 2020)
Introduction: The causes of lymphadenopathy may be varied ranging from reactive to neoplastic. Fine Needle Aspiration Cytology(FNAC) is a simple and inexpensive diagnostic tool to sample cells from superficial and accessible sites.Aims: This study was undertaken to assess the utility of FNAC in evaluating lymphadenopathy and to study the cytomorphological spectrum of lymph node lesions in our region.Settings and Design: A cross-sectional study of two years duration, on patients with lymphadenopathy who came to the Pathology Department for FNAC.Methods and materials: Cytology findings of Lymph node lesions were classified into four categories and were compared with histopathology diagnosis as the gold standard.Statistical Analysis: Data was tabulated according to various parameters. Sensitivity, Specificity, PPV, NPV, and Diagnostic accuracy for detecting malignancy were calculated.Results: The age range of patients included in the present study ranged from 9 to – 78 years. The mean age is 48.92 years and the median is 52 years. The cytological diagnosis was classified as reactive in 20 cases (32.7%), inflammatory in 16 cases (26.2%), lymphoma in 3 cases (4.9%), and 22 cases (36.1%) were metastasis from other sites. Following histopathology, the cases were diagnosed to be 19 reactive lymphadenopathies, 14 inflammatory lesions, 5 lymphomas, and 23 metastasis. The most common site of lymphadenopathy was the cervical region.Conclusions: FNAC has high sensitivity and specificity in differentiating benign lesions from malignant ones. The age, clinical findings, and supporting investigations should be taken into account while diagnosing a lesion as benign or malignant.